2016
DOI: 10.1364/ol.41.001443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of induced inner curvature on refractive index sensitivity in internally tilted long-period gratings

Abstract: A new complete analysis of the effect of induced inner curvature on refractive index (RI) sensitivity in internally tilted long-period gratings (ITLPGs) is presented. The responses in terms of RI sensitivity of a standard LPG and different ITLPGs with curvature values between 15 and 19  m-1 were compared. The analysis suggests first, that the larger the induced curvature, the greater the RI sensitivity; and second, that the RI sensitivity exponentially increases with both the curvature and cladding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…3 we present the resonance curves obtained for the three sensors for the refractive index of glycerol solution n s = 1.332 and different bending radii R. The resonance occurs at around 600 nm for all the investigated sensors and it shifts toward longer wavelengths in response to a curvature in− crease. Similar effect was observed for internally tilted long− −period gratings [29]. We clearly see in Fig.…”
Section: Resultssupporting
confidence: 85%
“…3 we present the resonance curves obtained for the three sensors for the refractive index of glycerol solution n s = 1.332 and different bending radii R. The resonance occurs at around 600 nm for all the investigated sensors and it shifts toward longer wavelengths in response to a curvature in− crease. Similar effect was observed for internally tilted long− −period gratings [29]. We clearly see in Fig.…”
Section: Resultssupporting
confidence: 85%
“…This structure essentially mimics the effect of an external bending of the optical fiber, while a straight configuration of the fiber is maintained. It was proved that the sensitivity to the surrounding RI changes of internally-tilted LPFGs is higher than standard LPFGs, considering the same cladding mode order, and this effect increases when greater tilt angles are realized [26]. Lastly, it is worth pointing out that chirped LPFGs, which represent another class of fiber gratings where the grating period increases monotonically according to a chirp value, can be also manufactured with the proposed experimental setup.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, this effect becomes larger when the realized inner curvature C (C = 1/R, R is the radius of curvature) of the grating planes increases as well (or R decreases) [25,26]. It was experimentally demonstrated that the previous effect follows a non-linear exponential behavior [26].…”
Section: Internally-tilted Lpfgsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results were corrected by taking into account the material dispersion of the solution RIs. In fact, in the case of water, the difference in RI reaches roughly 0.014 RIU and cannot be neglected when precise measurements are discussed and compared [37].…”
Section: Bioassay Protocol For Organophosphate Detectionmentioning
confidence: 99%